Kinerja Manajemen Rantai Pasok Sayuran Pada Perusahaan PT Petani Lokal di Kota Bandung - Najwa Fauzia Rahma; Eddy Renaldi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
PT Petani Lokal is an agribusiness company engaged in the production and distribution of fresh vegetables for modern retail markets. This study aims to analyze the vegetable supply chain structure and evaluate supply chain management performance at Petani Lokal using the Supply Chain Operations Reference (SCOR) Level 1 model. The research was conducted from August to October 2025 using a descriptive case study approach. The results indicate that Petani Lokal operates a fresh food supply chain with a direct supply chain structure. Supply chain performance assessment shows that the reliability and responsiveness attributes are classified as excellent, cost and asset management efficiency as good, and agility as average. The overall supply chain performance score is 77%, indicating good performance.